The Character Education Implementation and Local Wisdom Values in Learning History: The Islamic Development in Indonesia - Ramadani, Dilla Rizki; Fitrisia, Azmi (Universitas Jambi, Indonesia, 2023)
Learning process should not merely focus on school textbooks; however, paying attention to the local and traditional values should be there. This research aimed to produce the implementation of character education with local wisdom values in learning history, on the topic of Islamic development in Indonesia. This research used qualitative research with a case study approach. Data were collected through observations, interviews, and documents. The results indicated that the implementation of character education with local wisdom of Jambi's traditional Seloko was carried out by instilling religious education, honesty education, discipline education, creativity education, and social care education in students.